2020
DOI: 10.22271/chemi.2020.v8.i6c.10768
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of an underutilized crop: Browntop millet (Urochloa ramose)

Abstract: Browntop millet (Urochloa ramose L.) known as 'korale' in Karnataka is an annual warm-season grass often used as a forage crop gaining importance because of its nutritional qualities. Very fewer researches have been done so far on the millet. The research was conducted to determine the physical properties of the browntop millet. The physical properties were determined at moisture content 11.2 ± 0.16 (w.b). The mean values of length, width and thickness of the browntop millet were found to be 3.00 ± 0.21, 1.79 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…According to Saini and Sasmal (2022) the mass of 1,000 BTM grains was 3.66 ± 0.00 g. One thousand grains were counted, and afterwards, the weight of grains were recorded in grams to the closest one decimal point. Other studies conducted by Nagaraju et al (2020) and Titkare et al (2021) found the mean weight of 1,000 BTM seeds to be 3.42 ± 0.14 g and 2.49 g, respectively.…”
Section: Physiochemical Propertiesmentioning
confidence: 80%
See 2 more Smart Citations
“…According to Saini and Sasmal (2022) the mass of 1,000 BTM grains was 3.66 ± 0.00 g. One thousand grains were counted, and afterwards, the weight of grains were recorded in grams to the closest one decimal point. Other studies conducted by Nagaraju et al (2020) and Titkare et al (2021) found the mean weight of 1,000 BTM seeds to be 3.42 ± 0.14 g and 2.49 g, respectively.…”
Section: Physiochemical Propertiesmentioning
confidence: 80%
“…Bulk density of BTM was found to be 0.67 ± 0.00 g/ml by Sravani et al (2020). Nagaraju et al (2020) and Titkare et al (2021) have reported the bulk density of BTM grains to be 601.17 ± 4.08 kg/m3 and 545 kg/m3, respectively.…”
Section: Physiochemical Propertiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Millets are small-grained grasses that include proso millet (Panicum miliaceum), foxtail millet (Setaria italica), japanese barnyard millet (Echinochloa frumentacea), finger millet (Eleusine coracana), kodo millet (Paspalum scrobiculatum) (Ahmed S.M. et al, 2013; Michaelraj and Shanmugam, 2013) [2,35] browntop millet (Urochloa ramosa) (Nagaraju et al, 2020) [34] which are cultivated around the world. In the world small millets are popularly grown with an area of 31.24 million hectare with an annual production of 28.46 million tons.…”
Section: Introductionmentioning
confidence: 99%
“…In the world small millets are popularly grown with an area of 31.24 million hectare with an annual production of 28.46 million tons. India's contribution is much in millet production among other countries; the year 2017 witnessed a record millet production of 11.56 million tons with an area of 9.1 million hectare (Nagaraju et al, 2020) [34] . In recent years, millets are gaining importance in the worldwide because of their abundant nutritional values in terms of dietary fiber and low glycemic index (GI) value (Singh KP et al, 2012) [48] .…”
Section: Introductionmentioning
confidence: 99%